Textural analysis of strongly altered kimberlite : Examples from the Ekati diamond mine, Northwest Territories, Canada - Porritt, Lucy; Cas, Ray; Schaefer, Bruce; McKnight, Stafford (The Canadian Mineralogist, 2012)
Two massive, poorly sorted pyroclastic kimberlite deposits from the Fox and Koala pipes at the Ekati diamond mine, Northwest Territories, Canada present different styles of alteration. The first, at Fox, has an interstitial medium-alteration assemblage dominated by saponite, serpentine (lizardite), and microlitic diopside. The second, at Koala, has an alteration assemblage of serpentine (antigorite), carbonate, and minor saponite. They share the following sequence of events. Fine-grained matrix material has been serpentinized and replaced to varying degrees within each deposit, and the proportions of the preserved mineralogy of the interstitial medium reflect the nature and degree of alteration. Fine kimberlite ash is likely to have been hydrated and serpentinized soon after deposition by volcanic fluids percolating through the kimberlite vent fill deposits. Replacement, dissolution, and infilling of primary and secondary pore space are commonly observed textural features, and indicate that several phases of alteration have occurred, either as distinct episodes or, more likely, as part of a progressive sequence. The proportion of accessory lithic fragments contained within the deposits is much greater at Fox (15 to 35%) than at Koala (<10%) and has influenced the style of alteration in two ways. First, a greater proportion of cold lithic clasts acted as heat sinks and decreased the emplacement temperature of the Fox deposit as a whole. Second, a greater proportion of granodioritic lithic clasts, especially of smaller grain sizes, provided accessible sources of silica, aluminum, and calcium to the system, thus influencing the resulting alteration mineral assemblage.